Noise Suppression in Quadrature Phase-Shift-Keying-Oriented All-Optical Matching Systems Using Highly Nonlinear Fiber - Xin Li; Feiyang Ruan; Ying Tang; Tenglin Gao; Shanguo Huang (Photonics)
All-optical matching systems that detect and localize designated target sequences in input all-optical data sequences have attracted significant attention in all-optical processing. They have various applications, including all-optical intrusion detection, optical frame alignment, and optical package identification. In real-world applications, noise is inevitable and can lead to incorrect matching results. In particular, noise accumulates in serial all-optical matching systems, rendering the systems useless after several cycles. In this study, we developed a scheme for suppressing noise in quadrature phase-shift-keying (QPSK)-oriented all-optical matching systems. First, we evaluated the impact of input and amplifier noise on a QPSK-oriented all-optical matching system at a transmission rate of 100 Gbaud. We then developed a second-order noise-suppression structure using a highly nonlinear fiber (HNLF). With an input optical signal-to-noise ratio (OSNR) of 6 dB and an amplifier noise figure (NF) of 4 dB, the QPSK-oriented all-optical matching system without the noise-suppression structure output incorrect results. However, when the system was optimized using the proposed noise-suppression structure, correct matching results were obtained. Furthermore, when the NF of the amplifiers was fixed at 4 dB, the optimized system could reduce the minimum input OSNR to 0 dB. With an input OSNR of 0 dB, the logarithm of the bit error rate (BER) of the output matching results of the optimized system tended to negative infinity. The extinction ratio (ER), contrast ratio (CR), and quality (Q) factor of the output of the optimized system were 154.9532, 166.94289, and 161.12 dB, respectively, indicating high noise resistance. These results demonstrate that the system optimized using the proposed noise-suppression scheme exhibits high stability and reliability in noisy environments.